The wind knows my name eaudiobook A novel. - Allende, Isabel (Books on Tape, 2023)
NATIONAL BESTSELLER • “The lives of a Jewish boy escaping Nazi-occupied Europe and a mother and daughter fleeing twenty-first-century El Salvador intersect in this ambitious, intricate novel about war and immigration” ( People ), from the author of A Long Petal of the Sea and Violeta “Timely, provocative . . . emotionally satisfying . . . [a story about] the kindness of strangers who become family.”— The New York Times Book Review AN NPR BEST BOOK OF THE YEAR Vienna, 1938. Samuel Adler is five years old when his father disappears during Kristallnacht—the night his family loses everything. As her child’s safety becomes ever harder to guarantee, Samuel’s mother secures a spot for him on a Kindertransport train out of Nazi-occupied Austria to England. He boards alone, carrying nothing but a change of clothes and his violin. Arizona, 2019. Eight decades later, Anita Díaz and her mother board another train, fleeing looming danger in El Salvador and seeking refuge in the United States. But their arrival coincides with the new family separation policy, and seven-year-old Anita finds herself alone at a camp in Nogales. She escapes her tenuous reality through her trips to Azabahar, a magical world of the imagination. Meanwhile, Selena Durán, a young social worker, enlists the help of a successful lawyer in hopes of tracking down Anita’s mother. Intertwining past and present, The Wind Knows My Name tells the tale of these two unforgettable characters, both in search of family and home. It is both a testament to the sacrifices that parents make and a love letter to the children who survive the most unfathomable dangers—and never stop dreaming.